Passive transfer of collagen XVII-specific antibodies induces sustained blistering disease in adult mice - Chiriac Mircea Teodor; Licarete Emilia; Sas Alexandra Gabriela; Rados Andreea Maria; Lupan Iulia; Chiriac Anca Mirela; Speth Hilda; Pop-Vancia Vlad; Domsa Iacob; Sesarman Alina; Popescu Octavian; Sitaru Cassian (Orphanet Journal of Rare Diseases, 2013)
Abstract Background Bullous pemphigoid is a subepidermal blistering disorder associated with tissue-bound and circulating autoantibodies directed mainly to the hemidesmosomal component collagen XVII. While recapitulating the main immunopathological features of the human disease, frank skin blistering does not develop in the absence of skin rubbing in experimental pemphigoid models that have been established in neonatal mice. Moreover, due to their experimental design they only allow for short-term disease observation. In the present study we aimed to establish a model that reproduces the frank skin blistering seen in patients and allows for longer observation times. Methods Rabbit and sheep antibodies specific to several fragments of collagen XVII were generated and the purified antibodies were passively transferred into adult mice. Results Collagen XVII-specific IgG bound to the basal membrane of the skin and mucous membranes activating murine complement in vivo. Mice injected with collagen XVII-specific antibodies, in contrast to mice receiving control antibodies, developed frank skin blistering disease, reproducing human bullous pemphigoid at the clinical, histological and immunopathological levels. Titres of circulating IgG in the serum of mice correlated with the extent of the clinical disease. Mice receiving sheep antibodies specific to murine collagen XVII showed an early onset and a more active disease when compared to litter mates receiving specific rabbit antibodies. Conclusion This novel animal model for bullous pemphigoid should facilitate further investigations of the pathogenesis of bullous pemphigoid and the development of innovative therapies for this disease.